APLIKASI TEORI HEALTH BELIEF MODEL PADA PARTISIPASI WANITA USIA SUBUR (WUS) DALAM PEMERIKSAAN IVA DI KELURAHAN KALIBANTENG KULON - Inten Ayu Titisari; Emmy Riyanti; Priyadi Nugraha Prabamurti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Cervical cancer is one of the most suffered cancer by women in the world, especially in developing countries such as Indonesia. Cervical cancer is also the third leading cause of death in the world. So it’s necessary to do prevention, one of them is by conducting Visual Inspection of Acetic Acid (IVA). The purpose of this study was to analyze the relationship between several factors based on Health Belief Model’s theory with the participation of childbearing age women in IVA examination. This research was a quantitative study with a cross sectional approach. From a population of 926 childbearing woman that still sexually active in Kalibanteng Kulon Urban Village, 87 sample of childbearing age woman was obtained using the Lemeshow calculation and selection used simple random sampling technique. Data collection by interview using questionnaire. Data analysis carried out are univariate and bivariate with chi square test. Most respondents haven’t conducted an IVA examination (90.8%). Most of them were in young adults age, namely 18-39 years (67.8%), at the higher education level (67.8%), and married (100%). Most respondents have high knowledge (58.6%), high susceptibility perception (59.8%), high severity perception (56.3%), high benefits perception (64.4%), high barrier perception (52.9 %), lack of health worker support (62.1%) and lack of family support (66.7%). The results showed that the related variables were knowledge (p= 0.019), perception of barriers (p= 0.002), and health worker support (p= 0.049). It’s necessary to increase the role of health workers to increase childbearing age woman’s knowledge and reduce perceived barriers.